Depth profiling of ion-induced damage in D9 alloy using X-ray diffraction. Issue 3 (3rd April 2018) - Dey, S.; Gayathri, N.; Mukherjee, P.
ABSTRACT: The ion-induced depthwise damage profile in 35 MeV α-irradiated D9 alloy samples with doses of 5 × 10 15 He 2+ /cm 2, 6.4 × 10 16 He 2+ /cm 2 and 2 × 10 17 He 2+ /cm 2 has been assessed using X-ray diffraction technique. The microstructural characterisation has been done along the depth from beyond the stopping region (peak damage region) to the homogeneous damage region (surface) as simulated from SRIM. The parameters such as domain size and microstrain have been evaluated using two different X-ray diffraction line profile analysis techniques. The results indicate that at low dose the damage profile shows a prominent variation as a function of depth but, with increasing dose, it becomes more homogeneous along the depth. This suggests that enhanced defect diffusion and their annihilation in pre-existing and newly formed sinks play a significant role in deciding the final microstructure of the irradiated sample as a function of depth.